Burkitt-like lymphoma in an infant: a case report - Klumb,Claudete Esteves (2003)
Childhood non-Hodgkin's lymphomas, including Burkitt and Burkitt-like, are rarely diagnosed in infants. A case of B-cell lymphoma in a 13-month-old girl with extensive abdominal disease, ascites, pleural effusion, and tumor lysis syndrome is reported. Phenotypic analysis showed a germinal center B-cell phenotype, and a B-cell clonality was confirmed by polymerase chain reaction. There was no evidence of Epstein-Barr and HIV infection. The case herein reported emphasizes the need for considering the diagnosis of lymphoma even in very young children.